2022
DOI: 10.12688/f1000research.125645.1
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical profiling of Piper crocatum and its antifungal activity as Lanosterol 14 alpha demethylase CYP51 inhibitor: a review

Abstract: Mycoses or fungal infections are a general health problem that often occurs in healthy and immunocompromised people in the community. The development of resistant strains in Fungi and the incidence of azole antibiotic resistance in the Asia Pacific which reached 83% become a critical problem nowadays. To control fungal infections, substances and extracts isolated from natural resources, especially in the form of plants as the main sources of drug molecules today, are needed. Especially from Piperaceae, which h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…It can be suggested that compounds 1-3 have potential as new prospective candidate anti-fungal agents against C. albicans ATCC 10231. Some natural anti-fungal bioactive compounds against C. albicans ATCC 10231 were reported in some papers [57][58][59], but the anti-fungal activity of compounds 1-2 against C. albicans ATCC 10231 was reported for the first time in this research. This study adds to the list of natural anti-fungal compounds against C. albicans ATCC 10231.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…It can be suggested that compounds 1-3 have potential as new prospective candidate anti-fungal agents against C. albicans ATCC 10231. Some natural anti-fungal bioactive compounds against C. albicans ATCC 10231 were reported in some papers [57][58][59], but the anti-fungal activity of compounds 1-2 against C. albicans ATCC 10231 was reported for the first time in this research. This study adds to the list of natural anti-fungal compounds against C. albicans ATCC 10231.…”
Section: Discussionmentioning
confidence: 80%
“…Based on Table 4, ketoconazole, as the positive control, has zone inhibition of 30.0, 31.2, and 32.2 mm at concentrations of 2.5, 5, and 10% w/v, respectively, which means ketoconazole is a susceptible drug against C. albicans. This azoles group defines lanosterol 14α demethylase (ERG11) from ergosterol biosynthesis as a target protein against C. albicans, while the allylamines and thiocarbamates groups focused on squalane epoxidase (ERG1), the morpholines group on sterol 14∆ reductase (ERG24), the hydroxyanilides or amino-pyrazolinones group targeted on C-4 sterol methyl oxidase (ERG25), the C-4 sterol decarboxylase (ERG26), C-4 sterol ketoreductase (ERG27), and morpholines group focused on sterol 8∆ isomerase (ERG2), and the polyene macrolides group on C-24 sterol reductase (ERG4) in antifungal mechanisms [59,60]. Ergosterol is located along the C. albicans plasma membrane lipid bilayer consisting of bitopian endoplasmic reticulum proteins, which are coated by chitin, β-(1,3)-glucan, β-(1,6)-glucan, and mannoproteins which form galactosaminoglycan [64][65][66].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrates the potential for Red Betel leaf as an anti-fungal agent. The anti-fungal activity of P. crocatum Ruiz & Pav is derived from the secondary metabolite compounds contained therein, 75 as reported by multiple previous studies listed in Table 1 .…”
Section: Piper Crocatum Ruiz and Pav As Anti-infection Herbalmentioning
confidence: 92%
“…Antifungal mechanisms occur in fungal cells as a result of ergosterol inhibition induced by 5,6 desaturase (ERG3) inhibition [ 150 , 151 ]. Ergosterol is the most prevalent sterol in the fungal plasma membrane, and its binding to an ergosterol-specific enzyme can result in lanosterol demethylation [ 152 ]. The antimicrobial capacity of S. polyanthum is shown in Table 2 .…”
Section: Bioactivities Of S Polyanthum Leavesmentioning
confidence: 99%